2019
DOI: 10.1007/s40430-019-1785-9
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of processing methods for combustion pressure measurement in a diesel engine

Abstract: This paper analyzes combustion chamber pressure data processing methods related to the number of cycles averaged, top dead center referencing and pressure referencing (pegging). A total of 1000 consecutive engine cycles were measured in a four-cylinder diesel engine. The number of cycles that minimizes the influence of cycle-to-cycle oscillations depends on engine operating conditions and the parameters under analysis. The top dead center (TDC) referencing, using the motored curve, revealed that the thermodyna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…where a = 0:1 representing the desired percentage variation from the healthy conditions, wheras U(0, 1) denotes the standard uniform distribution from 0 to 1, and therefore x is a vector of the same size as B that contains uniformly distributed numbers from 0.95 to 1.05 in accordance to equation (26). The unknown parameters vector B is multiplied by a diagonal matrix containing the vector x in accordance by equation (27), which results to the degraded engine parameters vector B d .…”
Section: Case Studies Designmentioning
confidence: 99%
See 1 more Smart Citation
“…where a = 0:1 representing the desired percentage variation from the healthy conditions, wheras U(0, 1) denotes the standard uniform distribution from 0 to 1, and therefore x is a vector of the same size as B that contains uniformly distributed numbers from 0.95 to 1.05 in accordance to equation (26). The unknown parameters vector B is multiplied by a diagonal matrix containing the vector x in accordance by equation (27), which results to the degraded engine parameters vector B d .…”
Section: Case Studies Designmentioning
confidence: 99%
“…24 Moreover, having measured the in-cylinder pressure, the non-trivial task of signal correction is required, in order to remove the noise and perform averaging over several cycles, and most importantly to remove offsets by calibrating the acquired signal with respect to the engine crank angle 25 and the cylinder pressure. 26 As a result, methodologies have been developed utilising alternative engine measurements to predict important features that belong to, or can be directly derived from the in-cylinder pressure diagrams in a reliable and low-cost manner. In specific, for automotive industry applications, the peak pressure position has been predicted using accelerometers mounted on every cylinder, 27,28 as well as an ICT sensor.…”
Section: Introductionmentioning
confidence: 99%
“…However, this is a time consuming and inefficient process. An attempt was made to correct for this problem by introducing a socalled ''characteristic variation'' (C i ) weighting factor, as shown in equation (6).…”
Section: Relative Error Formulation Selectionmentioning
confidence: 99%
“…The conclusion was that 50 cycles were sufficient for calculating a stable value of IMEP and its COV for this set of data. da Silva et al 6 explored the effect of ensemble length in the COVs of IMEP and Peak Cylinder Pressure (PCP) for ensembles presenting cycle-to-cycle variability. This study demonstrated that that the sufficient number of cycles that minimizes cycle-to-cycle variation effects on calculated parameters from cylinder pressure and heat release was dependent on engine operating conditions and the analyzed parameter, ranging from 250 to 850 cycles.…”
Section: Introductionmentioning
confidence: 99%
“…Piezo-electric pressure sensors, as are normally used to measure cylinder pressures, must be tied to a known absolute pressure to obtain the effective in-cylinder pressure. The most common pegging methods are either based on a thermodynamic calculation assuming a fixed polytropic exponent within a part of the engine cycle, or based on the assumption that the cylinder pressure is equal to the intake manifold pressure at a certain point during the engine cycle [26]. In the case of the Flex-OeCoS, the first method is difficult to apply due to the different wall-heat transfer regimes in the engine cylinder, the optically accessible combustion chamber and the connecting "neck" in-between.…”
Section: Pegging Of the Cylinder Pressurementioning
confidence: 99%